Adsorption capacities of carbon dioxide, oxygen, nitrogen and methane on carbon molecular basket derived from polyethyleneimine impregnation on microporous palm shell activated carbon - Aroua, M.K.; Daud, W.M.A.W.; Yin, C.Y.; Adinata, D. (Separation and Purification Technology, 2008)
In this study, palm shell-based activated carbon (AC) was used as precursor in the production of carbon molecular basket (CMB) via impregnation of polyethyleneimine (PEI). The effects of amount of PEI impregnated on AC on carbon dioxide (CO2), oxygen (O2), nitrogen (N2), and methane (CH4) adsorption capacities of CMB were investigated. Molecular basket was produced at PEI weight percentages of 0.06, 0.11, 0.13, 0.26, 0.27 and 0.28 wt%. Adsorption capacities of CO2, O2, N2 and CH4 were enhanced with increasing PEI impregnation from virgin AC to 0.26 wt% PEI/AC before the capacities decreased onwards for 0.28 and 0.29 wt% PEI/AC. The amount of PEI impregnation determined for optimum uptake of gas adsorption was 0.26 wt% PEI/AC. The maximum adsorption capacity for the gases follows the sequence: CO2 ≫ CH4 > O2 > N2 for all the CMB samples.